Spoken language interaction with robots: Recommendations for future research. (January 2022) - Marge, Matthew; Espy-Wilson, Carol; Ward, Nigel G.; Alwan, Abeer; Artzi, Yoav; Bansal, Mohit; Blankenship, Gil; Chai, Joyce; Daumé, Hal; Dey, Debadeepta; Harper, Mary; Howard, Thomas; et al.
Abstract: With robotics rapidly advancing, more effective human–robot interaction is increasingly needed to realize the full potential of robots for society. While spoken language must be part of the solution, our ability to provide spoken language interaction capabilities is still very limited. In this article, based on the report of an interdisciplinary workshop convened by the National Science Foundation, we identify key scientific and engineering advances needed to enable effective spoken language interaction with robotics. We make 25 recommendations, involving eight general themes: putting human needs first, better modeling the social and interactive aspects of language, improving robustness, creating new methods for rapid adaptation, better integrating speech and language with other communication modalities, giving speech and language components access to rich representations of the robot's current knowledge and state, making all components operate in real time, and improving research infrastructure and resources. Research and development that prioritizes these topics will, we believe, provide a solid foundation for the creation of speech-capable robots that are easy and effective for humans to work with. Highlights: It is now time for human needs to be the main driver of research in this area. Wide utility requires advances in robustness, adaptability, and controllability. Making robots more speech-capable will require richer internal representations. Highly interactive dialogue requires incremental and realtime processing throughout. Basic research in realtime social interaction is still needed.